2022
DOI: 10.1371/journal.pone.0262101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity among Kuwaiti adolescents and the perception of body weight by parents or friends

Abstract: Objective Recently, the State of Kuwait has witnessed a steady rise in the prevalence of obesity among children and adolescents. The present study aims to provide an update on the rate of overweight or obesity among Kuwaiti adolescents and examines the associations between adolescents’ overweight/obesity levels and their perception of body weight as seen by parents or friends. Methods A cross-sectional study was conducted in Kuwaiti secondary schools and included adolescents between the ages of 15 and 18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Twenty-one articles incorporated in the systematic review were published between the years 2018 and 2023. Four studies originated from Jordan, [44][45][46][47] four from Saudi Arabia, [48][49][50][51] two each from Kuwait, 52,53 Palestine, 54,55 UAE, 56,57 Algeria, 58,59 and Qatar, 60,61 and one each published from Sudan, 62 Egypt, 63 and Iran. 64 Studies enrolled children between 1 and 19 years old.…”
Section: Attributes Of Included Studiesmentioning
confidence: 99%
“…Twenty-one articles incorporated in the systematic review were published between the years 2018 and 2023. Four studies originated from Jordan, [44][45][46][47] four from Saudi Arabia, [48][49][50][51] two each from Kuwait, 52,53 Palestine, 54,55 UAE, 56,57 Algeria, 58,59 and Qatar, 60,61 and one each published from Sudan, 62 Egypt, 63 and Iran. 64 Studies enrolled children between 1 and 19 years old.…”
Section: Attributes Of Included Studiesmentioning
confidence: 99%
“…Understanding the compatibility of health delivery methods is the main thing in providing good feedback from respondents. It is very important to design nutrition education programs that are effective and adapted to this population (15). Nutrition education is part of preventive medicine.…”
Section: Nutrition Education On the Knowledge Of Pregnant Womenmentioning
confidence: 99%
“…A study in Sweden shows that up to 83% of adolescents eat out with their friends, consuming high-energy foods and drinks such as tea, coffee, cakes, and cookies 51 . Peers also influence adolescents' BMI; the influence of peers on adolescents' BMI is that there is a prevailing social norm among adolescents regarding body size, where adolescents with overnutrition report lower self-esteem and body satisfaction and receive teasing about their weight from peer 52 . Therefore, interactions between adolescents and peers can affect their body perception through conversations related to appearance, modelling of peer diet behaviour, and perceptions of attitudes related to peer appearance 53 Research found that an increase in peers' BMI increases adolescents' BMI and the likelihood of overweight and obesity 54 .…”
Section: Relationship Between Variablesmentioning
confidence: 99%